ANALYSING THE UNIQUE CURRICULUM OF AN ISLAMIC SCHOOL IN DUBAI: A QUALITATIVE STUDY - Preece, Abdul Shakour Duncan; Suleiman Majid, Sharifa (2013)
The study aims to analyse and explore the unique philosophy adopted by an Islamic School in Dubai called ‘Islamic School for Training & Education (ISTE). The study will also look at the effects of the school’s philosophy on its curriculum and instruction. In addition to studying written documents about the school and its curriculum, the researchers have collected qualitative data from teachers, students, parents and administrators to ascertain the feasibility of the project and gauge their reactions to this new and radical approach to education.